Rain splash-mediated dispersal of Escherichia coli from fecal deposits to field-grown lettuce in the mid- and south Atlantic U.S. regions is affected by mulch type - Hopper, Adam L.; Hudson, Claire L.; Klair, Diksha; Ding, Qiao; Gao, Zhujun; Jha, Aprajeeta; Bryan, Austin; Tikekar, Rohan V.; Coolong, Timothy; Dunn, Laurel L.; Micallef, Shirley A. (Frontiers in Plant Science, 2024)
Wildlife feces can contaminate vegetables when enteric bacteria are released by rain and splashed onto crops. Regulations require growers to identify and not harvest produce that is likely contaminated, but U.S. federal standards do not define dimensions for no-harvest zones. Moreover, mulching, used to retain soil moisture and maximize crop yield may impact rainmediated bacterial dispersal from feces. To assess Escherichia coli dissemination from a fecal point source to lettuce grown on various mulches, lettuce cv. 'Magenta' was transplanted into raised beds with plastic, biodegradable plastic, straw, or left uncovered at field sites in Maryland and Georgia. Eleven days post-transplant, 10 g of rabbit manure spiked with ~8 log CFU g -1 E. coli were deposited in each bed. One day following natural or simulated rain events, lettuce was sampled along 1.5 m transects on either side of fecal deposits. Lettuce-associated E. coli was semi-quantified with an MPN assay and dependence on fecal age (stale or fresh), lettuce age (baby leaf or mature head), distance from point source, mulch and post-rain days were statistically evaluated. Distance (p<0.001), fecal age (p<0.001) and mulch (p<0.01) were factors for E. coli transfer from point source to lettuce. The highest and lowest E. coli estimates were measured from lettuce grown on biodegradable plastic and straw, respectively, with a 2-log MPN difference (p<0.001). Mulch and distance were also significant factors in E. coli recovery 3 days post-rain (both p<0.001), where plastic mulches differed from bare ground and straw (p<0.01). For all treatments, fewer E. coli were retrieved from lettuce at 0.3 m, 3 days post-rain compared to 1 day (p<0.001). Fitting the data to a Weibull Model predicated that a 7-log reduction in E. coli from fecal levels would be achieved at 1.2-1.4 m from the point source on plastic mulches, 0.75 m on bare soil (p<0.05) and 0.43 m on straw (p<0.01). Straw and bare ground limited rainmediated E. coli dispersal from feces to lettuce compared to plastic mulches. Fecal age was negatively associated with E. coli dispersal. These findings can inform harvesting recommendations for measures related to animal intrusion in vegetable production areas.